Fostering a Literate U.S. Workforce: Perspectives of Adult Educators in Human Resource Development - Merlissa C. Alfred (Adult Education Research Conference, 2010)
Organizations are faced with increasing demands for a highly literate and skilled workforce. Investments in basic literacy and skills training are required to effectively address these organizational needs. The purpose of this study was to investigate Human Resource Development’s role in investing in and developing the segment of the US workforce that lacks the basic literacy and skills needed to participate in the employment arena.
Keywords: adult literacy; adult education; human resource development